Comparison of yield and complications of craniocaudal versus caudocranial needle trajectory for kidney biopsy. Issue 1 (January 2020) - Prasad, Narayan; Shukla, Rahul; Behera, Manas; Yachha, Monika; Bhadauria, Dharmendra; Kaul, Anupama; Lal, Heera; Gupta, Amit
Background: Percutaneous renal biopsy can result in serious complications. The study is aimed to compare the safety and yield between the two approaches of biopsy techniques: the conventional craniocaudal and the caudocranial trajectory of the biopsy needle under real-time ultrasound guidance. Methods: In this prospective observational study, a total of 80 serial kidney biopsies were performed, 40 with craniocaudal angulation and 40 with caudocranial angulation of the biopsy needle on the random allocation of 1:1 in each group. In the craniocaudal approach, the patient must hold the breath in deep inspiration to make a lower pole of the kidney approachable during unloading the biopsy gun, which was not required in caudocranial trajectory as the lower pole was approachable without holding the breath in deep inspiration. All kidney biopsies were performed percutaneously under real-time ultrasonogram guidance with a 16-cm-long, 16- or 18-gauge needles with a penetration depth of 22 mm and a sample notch of 18 mm. The yield and complications between the two groups were analyzed. Results: Both the groups were comparable in essential demographic characteristics. The study found that the caudocranial position of renal biopsy is equally suitable concerning tissue yield without any increase in the risk of complications and a smaller number of passes to obtain adequate tissue. Conclusion: Caudocranial trajectory of the biopsy needle using a probe needle guide is as safe as the craniocaudal approach. Both approaches have similar yield and complications; however, the caudocranial approach provides ease to the patient during the procedure.